The compatibility of earth-based repair mortars with rammed earth substrates - Gomes, I. (2013)
Earth constructions are susceptible to degradation due to natural or human causes. The degradation of the exterior surface of earth walls is very common, either due to lack of maintenance or to the use of incompatible materials, and often requires the application of a repair mortar. This work experimentally analyses the performance of earth-based repair mortars applied on rammed earth surfaces. The mortars are based on earth collected from rammed earth buildings in south Portugal or on a commercial earth. Eight repair mortars were formulated, with the unstabilized soils or including a small binder content. Four types of binder were tested: hydrated air-lime, natural hydraulic lime, Portland cement and natural cement. The repair mortars were applied on two types of standard defects purposely made on rammed earth blocks, representing the most current common defects found on exterior rammed earth surfaces: a standard superficial defect and a standard deep defect. The performance of the mortars, their compatibility with the substrates and the visual effectiveness of the intervention were evaluated. It was concluded that the mortars behaved differently when applied on different rammed earth supports. However, the best performances occurred always for the mortars made from unstabilized soil identical to that of the rammed earth substrate. Indeed, the use of stabilizers systematically worsened the behavior of the repair mortars, regardless of the type of binder used for that purpose.